The Impact of Enterprise Management Efficiency on Human Capital - Li, Yanfei; Apibunyopas, Jeerakiat (Science, Technology, and Social Sciences Procedia, 2023)
The 2 main research objectives of this paper are to examine the relationship between firm management efficiency and the effect of human capital accumulation, and to examine the relationship between firm management efficiency and the level of vocational education of employees. This paper collects information through a questionnaire and conducts a study of the questions. Our statistical questionnaire is aimed at enterprises in Hainan Province, China. At the same time, 2 questionnaires were prepared to collect data. On the basis of collecting and sorting out the data, the statistical analysis is carried out to verify the 2 hypotheses proposed in this paper. A total of 3,500 company questionnaires and employee questionnaires were distributed. Among them, some enterprises and employees have default values and outliers in the indicators, which are eliminated and sorted. In the end, 2980 valid questionnaires were obtained. Using the data obtained from the questionnaire, this paper conducts a large sample empirical study on the impact of enterprise management efficiency scores on enterprise human capital accumulation from the labor level. The benchmark regression results show that the management efficiency score has a significant promoting effect on the human capital accumulation of enterprises. Enterprises with higher management efficiency scores have more staff communication frequency, longer reading and learning time, more professional skills training and physical exercise.